Photo-polymerisation variables influence the structure and subsequent thermal response of dental resin matrices. Issue 3 (March 2020) - Sirovica, Slobodan; Guo, Yilan; Guan, Raymond; Skoda, Maximilian W.A.; Palin, William M.; Morrell, Alexander P.; Romanyk, Dan L.; Martin, Richard A.; Addison, Owen
Highlights: Initial polymer structure; influenced by photo-polymerisation variables, impacts the thermal response of resin matrices. Systems polymerised rapidly are more influenced by thermal perturbation. Accelerating polymerisation confers reduced chain extension below the glass transition temperature. Slower polymerised systems display greater relative order before and after the glass transition point. Abstract: Objective: The structure of the polymer phase of dental resin-based-composites is highly sensitive to photo-polymerisation variables. The objective of this study was to understand how different polymer structures, generated with different photo-polymerisation protocols, respond to thermal perturbation. Methods: Experimental resins were prepared from a series of Bis-GMA/TEGDMA blends (40/60, 50/50 and 60/40 wt.%), with either Camphorquinone/DMAEMA or Lucirin TPO as the photo-initiator system. Resins were photo-polymerised, in a disc geometry, at either relatively 'high' (3000 mW cm −2 for 6 s) or 'low' (300 mW cm −2 for 60 s) irradiances ensuring matched radiant exposures (18 J cm −2 ). Specimens were heated, from 20−160 °C at a rate of 5 °C min −1, whilst simultaneous synchrotron X-ray scattering measurements were taken at 5 °C increments to determine changes in polymer chain segment extension and medium-range order as a function of temperature. For each unique resin composition (n = 3), differential scanning calorimetry was used to measure glass transition temperatures using the same heating protocol. A paired t-test was used to determine significant differences in the glass transition temperature between irradiance protocols and photo-initiator chemistry at ɑ = 0.05. Results: Resins pre-polymerised through the use of TPO and or high irradiances demonstrated a reduced rate of chain extension indicative of lower thermal expansion and a larger decrease in relative order when heated below the glass transition temperature. Above the transition temperature, differences in the rate of chain extension were negligible, but slower converted systems showed greater relative order. There was no significant difference in the glass transition temperature between different photo-initiator systems or irradiance protocols. Significance: The evolution of chain extension and medium-range order during heating is dependent on the initial polymer structure which is influenced by photo-polymerisation variables. Less ordered systems, generated at faster rates of reactive group conversion displayed reduced chain extension below the glass transition temperature and maintained lower order throughout heating.